2022
DOI: 10.1093/eurheartj/ehac544.802
|View full text |Cite
|
Sign up to set email alerts
|

Risk of heart failure following short-term non-steroidal anti-inflammatory drug use in patients with type 2 diabetes mellitus

Abstract: Background Fluid retention is a known but underappreciated side-effect of non-steroidal anti-inflammatory drug (NSAID) use. As type 2 diabetes mellitus (T2DM) has been linked to both subclinical cardiomyopathy and a decline in kidney function, short-term NSAID use could lead to subsequently development of heart failure (HF) due to aberrations in fluid balances. Purpose We investigated associations between short-term NSAID use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…8 Particularly noteworthy was the observed association among subgroups aged 80 years or older (OR: 1.78; 95% CI: 1.39-2.28). 8 However, other findings from ASPREE study 10 and ASCEND study 19 did not show enough evidence of a statistically significant effect of aspirin on incident heart failure in the study population. Although large cohort studies indicated a lack of significant benefit of aspirin for primary prevention in older individuals, 10,11 the clinical relevance of the association between aspirin use and the risk of heart failure was deemed to be limited based on the current studies.…”
Section: Disscussionmentioning
confidence: 92%
See 3 more Smart Citations
“…8 Particularly noteworthy was the observed association among subgroups aged 80 years or older (OR: 1.78; 95% CI: 1.39-2.28). 8 However, other findings from ASPREE study 10 and ASCEND study 19 did not show enough evidence of a statistically significant effect of aspirin on incident heart failure in the study population. Although large cohort studies indicated a lack of significant benefit of aspirin for primary prevention in older individuals, 10,11 the clinical relevance of the association between aspirin use and the risk of heart failure was deemed to be limited based on the current studies.…”
Section: Disscussionmentioning
confidence: 92%
“…The HOMAGE study firstly provided evidence reporting an elevated risk (adjusted hazard ratio [HR]: 1.26; 95% CI: 1.12–1.41) of heart failure among individuals at risk for heart failure who use aspirin 9 . In another large observational study involving 331 189 participants, the use of short‐term NSAIDs was shown to be associated with an increased risk of hospitalization due to heart failure (OR: 1.43; 95% CI: 1.27–1.63) 8 . Particularly noteworthy was the observed association among subgroups aged 80 years or older (OR: 1.78; 95% CI: 1.39–2.28) 8 .…”
Section: Disscussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A study recently presented at the 2022 Congress of the European Society of Cardiology (ESC) revealed that short-term NSAID use could potentially augment the chance of first-time HF in patients having T2DM [15]. A greater than 40% increase in the likelihood of hospitalization for first-time HF in patients who took NSAIDs, including ibuprofen, the most widely used drug, was observed.…”
mentioning
confidence: 99%